Sovietinės lietuvių istoriografijos raidos lūžių paieškos: 1956 metai(?) - Švedas, Aurimas (Lietuvos istorijos studijos, 2007)
The XX Congress of the Soviet Union Communist Party which took place in February 1956 became a symbol of radical reforms in the Soviet Union. Liberation processes started in many fields of the totalitarian state: in political and social life, in culture, in science, and art. New changes rapidly reached allied Soviet republics where "thaw" also began. This article raises the question: Was the year 1956 the beginning of new discourses, polemics, and "revolt" against old methodological-ideological postulates in the Soviet Lithuanian historiography? The illusion of possible changes in history research in 1956 was created by the Lithuanian Communist Party (LCP) itself, which organized several meetings with Lithuanian intellectuals discussing the short history of Soviet Lithuania prepared by the History Institute. The Central Committee Bureau of LCP wanted to find out whether the official discourse introduced by the Bureau and by the director of the Institute Žiugžda follows the requirements of new conditions and whether this discourse is resistant to the possible accuses for political and ideological "mistakes" which could have come from Moscow. The intents of the Central Committee of LCP were misunderstood by some humanitarians who, during the general session of the Science Academy in February 1956, tried to provoke the discussion on the current situation in the History Institute and to propose a new director of the Institute. The elite of LCP ruined the possibility of radical changes by supporting Žiugžda and his scientific opponents were accused of "bourgeois nationalism". For this reason, the year 1956 in Lithuanian Soviet historiography did not become the beginning of radical changes but rather the period of status quo. With the changes of the Soviet system, this status quo also altered gradually giving historians more "freedom of manoeuvre". However, we could not speak about a quick and essential "thaw" in the Soviet Lithuanian historiography after 1956.